Characterization of fluorescent nuclear track detectors as criticality dosimeters. (November 2017) - Harrison, J.; Moreno, B.; Van Hoey, O.; Mihailescu, L.-C.; Vanhavere, F.; Million, M.; Fomenko, V.; Akselrod, M.
Abstract: Fluorescent nuclear track detectors (FNTDs) are suggested for criticality dosimetry of neutrons and photons. The depth profiles of the fluorescent signal from FNTDs after exposure to high doses of broad spectrum neutron fields from four different sources are analyzed using the power spectrum integral (PSI) measured at increasing depths within the Al2 O3 :C, Mg crystals. The depth profiles are compared to Monte Carlo simulations of energy deposition of recoil protons as a function of depth in aluminum oxide for the same four neutron sources. An algorithm for estimating the median neutron energy and neutron dose correction factors was developed. The application of FNTDs for criticality excursion accidents is discussed. Highlights: FNTD technology is suggested for criticality dosimetry. FNTD signal depth profiles were obtained for four different neutron sources. Monte Carlo simulations of energy deposition by recoil protons in aluminum oxide crystal fit well the experimental data. The depth profile of the FNTD signal can be used for estimation of median neutron energy and neutron dose correction factor.